First European data from the network of severe allergic reactions (NORA). - Worm, M; Moneret-Vautrin, A; Scherer, K; Lang, R; Fernandez-Rivas, M.; Cardona, V.; Kowalski, M. L.; Jutel, M.; Poziomkowska-Gesicka, I; Papadopoulos, N. G.; Beyer, K.; Mustakov, T.; et al. (Allergy, 2014)
BACKGROUND: Occurrence, elicitors and treatment of severe allergic reactions are recognized and reported differently between countries. We aimed to collect standardized data throughout Europe on anaphylaxis referred for diagnosis and counselling. METHODS: Tertiary allergy, dermatology and paediatric units in 10 European countries took part in this pilot phase of the first European Anaphylaxis Registry, from June 2011 to March 2014. An online questionnaire was used to collect data on severe allergic reactions based on the medical history and diagnostics. RESULTS: Fifty-nine centres reported 3333 cases of anaphylaxis, with 26.7% below 18 years of age. Allergic reactions were mainly caused by food (children and adults 64.9% and 20.2%, respectively) and insect venom (20.2% and 48.2%) and less often by drugs (4.8% and 22.4%). Most reactions occurred within 30 min of exposure (80.5%); a delay of 4+ hours was mainly seen in drug anaphylaxis (6.7%). Symptom patterns differed by elicitor, with the skin being affected most often (84.1%). A previous, usually milder reaction to the same allergen was reported by 34.2%. The mainstay of first-line treatment by professionals included corticoids (60.4%) and antihistamines (52.8%). Only 13.7% of lay- or self-treated reactions to food and 27.6% of insect anaphylaxis received on-site adrenaline. CONCLUSION: This pilot phase of a pan-European registry for severe allergic reactions provides for the first time data on anaphylaxis throughout Europe, demonstrates its potential functionality and allows a comparison of symptom patterns, elicitors and treatment habits between referral centres and countries.